Leadership Style Impact to Employees Satisfaction in Honey Industry Companies (Journal of Innovation, Business and Entrepreneurship, 2020)
The purpose of this study was to determine the effect of transformational and transformational leadership styles on employee job satisfaction in honey industry companies in Indonesia. Achieving employee job satisfaction is very important to maintain productive and efficient employees and maintain good company performance. Therefore, one way that might be effective in helping company leaders increase satisfaction among their followers is to use the right leadership style. The study population consisted of all employees in the honey industry company in Indonesia. There are already 85 respondents from 2 large companies in the honey industry. Regarding transformational leadership and transactional leadership, the survey was adapted from the Multifactor Leadership Questionnaire (MLQ). Then job satisfaction was measured by The Minnesota Satisfaction Questionnaire (MSQ) developed by Weiss in 1967. The analytical method used was quantitative method, statistical analysis method consisting of multiple linear regression analysis, partial significant testing (t-test), testing simultaneous significance (F-Test) and testing the coefficient of determination (R2). The results of this study are that there is a significant and positive influence between the dimensions of transformational leadership and transactional leadership on employee job satisfaction. The transformational leadership variable has the most dominant influence on employee job satisfaction. Therefore, it would be better if the honey industry company applied a combination of transformational and transactional leadership styles to increase the job satisfaction of its employees.Keywords: honey industry companies, transformational leadership, transactional leadership, employees satisfaction